How have pensioner incomes and poverty changed in recent years? - Jonathan Cribb; Anna Henry; Heidi Karjalainen (Institute for Fiscal Studies (IFS), 2024)
This report examines the key trends in pensioner incomes and poverty over the past two decades.
Keywords: 330; Poverty; inequality and social mobility; Savings; pensions and wealth; Ageing; Benefits; Employment; Inequality; Living standards; Pensioner benefits; Poverty; Retirement; Savings; State pensions